Global diversity and distribution of nitrogen-fixing bacteria in the soil - Sepp, Siim-Kaarel; Vasar, Martti; Davison, John; Oja, Jane; Anslan, Sten; Al-Quraishy, Saleh; Bahram, Mohammad; Bueno, C. Guillermo; Cantero, Juan José; Fabiano, Ezequiel Chimbioputo; Decocq, Guillaume; Drenkhan, Rein; et al. (Frontiers in Plant Science, 2023)
Our knowledge of microbial biogeography has advanced in recent years, yet we lack knowledge of the global diversity of some important functional groups. Here, we used environmental DNA from 327 globally collected soil samples to investigate the biodiversity patterns of nitrogen-fixing bacteria by focusing on the nifH gene but also amplifying the general prokaryotic 16S SSU region. Globally, N-fixing prokaryotic communities are driven mainly by climatic conditions, with most groups being positively correlated with stable hot or seasonally humid climates. Among soil parameters, pH, but also soil N content were most often shown to correlate with the diversity of N-fixer groups. However, specific groups of N-fixing prokaryotes show contrasting responses to the same variables, notably in Cyanobacteria that were negatively correlated with stable hot climates, and showed a U-shaped correlation with soil pH, contrary to other N-fixers. Also, the non-N-fixing prokaryotic community composition was differentially correlated with the diversity and abundance of N-fixer groups, showing the often-neglected impact of biotic interactions among bacteria.